Perfil sensorial de crianças com Síndrome de Down na perspectiva dos familiares - Casotti, Jamilli Melo (2025)
Children with Down Syndrome (DS) or Trisomy 21 (T21) present significant delays in neuropsychomotor development, thus suffering from multifactorial interferences such as intellectual deficit, physical, behavioral, social, and sensory alterations. All these interferences can directly or indirectly impact their participation in occupations. Among these interferences, sensory issues are shown to be an important factor impacting good occupational engagement. It is known that for a child to participate in their occupations, their Central Nervous System needs to organize the sensory information received from the environment and their own body, and then plan and execute effective actions so that they can interact in their different contexts. This process is called "Sensory Integration." When this process does not occur as expected, a condition of Sensory Dysfunction arises, which interferes with the child's engagement and occupational repertoire. Initial research highlights atypical sensory processing profiles in children with Down syndrome; however, the need for further studies to deepen this understanding is evident. Therefore, this study aims to investigate the sensory profile of children with Down syndrome, aged 3 to 12 years, from the perspective of their families, and to identify if there is a prevalence of a sensory processing pattern in this population. This is a descriptive, cross-sectional, exploratory study with a quantitative approach. The research was conducted in person at a private service in the city of São Paulo, Brazil, and remotely via the Google Meet platform. The standardized instrument "Sensory Profile-2 of the Child," in its translated and transculturally adapted version for Brazilian children and adolescents, was used. The research indicated a sensory performance different from their peers, mainly in the "movement processing" sensory section, but differences in responses can be observed in other sensory sections such as visual, tactile, vestibular, oral, and auditory processing. In the "Seeking Stimulation" quadrant, a different sensory processing pattern compared to their peers was also observed, with responses such as "more or much more than others" prevailing. In the behavioral section, the response alternative "like most others" prevailed for the three categories evaluated (conduct, socio-emotional, and attentional), however, there were also responses different from their peers, highlighting the importance of discussing the impact of unexpected performance on the behavior of children with Down syndrome. The findings of this research corroborate data from other studies and strengthen the evidence related to the sensory profile of children with Down syndrome, especially when analyzing the sections of the first part of the instrument, regarding the sensory processing of each system, which can interfere with activities of daily living such as hygiene, dressing, eating, among other aspects, thus potentially disrupting family routines. Children with Down syndrome may present different responses in sensory processing compared to their peers, which can interfere with engagement in daily occupations and their various contexts, thus requiring targeted strategies to achieve success in their participation.